SPEECH ERRORS ANALYSIS PRODUCED BY AUTISTIC CHARACTER IN WHAT’S EATING GILBERT GRAPE? FILM - Rabbanyyah, Aisyah Faza; Zamruddin, Mardliya Pratiwi; Setyowati, Ririn (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
This study is aimed to find out the types and the causes of speech error in the autism character named Arnie in What’s Eating Gilbert Grape? film. The theory used to find out the speech errors of Arnie was Clark and Clark’s theory, they are repeats, false starts, pause, corrections, stutters and slips of the tongue. Words, phrases and sentences in the form of dialogues by Arnie were the data in this study. The research design of this study was qualitative. The results showed the speech errors in Arnie’s utterances were identified into four types namely repetitions, false starts, pause and stutter. The speech errors are caused by cognitive difficulty and social factors which are divided again into situational anxiety and social circumstances. Arnie produced speech errors that were caused by cognitive difficulty that happen because the speaker has autism disorder and there is a problem in his brain to process his speech properly. Furthermore, the social factor, which are situational anxiety factor of speech error happen when Arnie feels anxious and nervous, then social circumstances influenced the speech error when Arnie uncomfortable with his circle.